Analisis Kepustakaan tentang Undang-Undang Guru dan Dosen di Lembaga Pendidikan Islam - Muhajir, Ahmad (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2024)
This research aims to explore the role of Law No 14/2005 on Teachers and Lecturers in improving the quality of education in Islamic education institutions in Indonesia through a literature study. The results show that the implementation of this law in Islamic education institutions varies. Some institutions have successfully adopted and implemented it well, while others face various obstacles, including budget limitations, lack of understanding of the law and variations in the quality of management. In institutions that have successfully implemented it, there have been improvements in the quality of education, the motivation and welfare of teachers and lecturers, and consistency in teaching. Support from the government and relevant agencies is essential to improve the implementation of this law, through budget assistance, ongoing training programmes, and socialisation and education about the law. Management capacity building in Islamic education institutions and improving the welfare of teachers and lecturers are also important factors in supporting the successful implementation of this law. This study concludes that the Teachers and Lecturers Law has great potential to improve the quality of education in Islamic education institutions but its success depends on various supporting factors. Further research is needed to evaluate the long-term impact and broaden the focus of the study to get a more comprehensive picture.